CHADS2 Score/CHA2DS2-VASc Score and Major Artery Occlusion in Cardioembolic Stroke Patients with Nonvalvular Atrial Fibrillation. Issue 5 (July 2014) - Deguchi, Ichiro; Hayashi, Takeshi; Ohe, Yasuko; Kato, Yuji; Fukuoka, Takuya; Maruyama, Hajime; Horiuchi, Yohsuke; Sano, Hiroyasu; Nagamine, Yuito; Tanahashi, Norio
Objective: The associations between the CHADS2 score/ CHA2 DS2 -VASc score, and the presence of cerebral vessel occlusion on admission were examined in cardioembolic stroke patients with nonvalvular atrial fibrillation. Methods: The subjects were 546 consecutive patients hospitalized between April 2007 and December 2012 with onset of cardioembolic stroke associated with nonvalvular atrial fibrillation within 24 h. The associations between the CHADS2 score/CHA2 DS2 -VASc score and the presence of occluded cerebral vessels on magnetic resonance angiography were evaluated retrospectively. Occluded cerebral vessels were classified into the internal carotid artery, middle cerebral artery (M1, M2), basilar artery, and other (anterior cerebral artery [A1], posterior cerebral artery [P1], vertebral artery). Results: Major artery occlusion was seen in 52% of patients with CHADS2 score 0, 52% of patients with score 1, 57% with score 2, 75% with score 3, and 75% with score ≥4. As for the CHA2 DS2 -VASc score, major artery occlusion was seen in 62% of patients with score 0, 49% with score 1, 53% with score 2, 53% with score 3, 65% with score 4, 71% with score 5, and 82% with score ≥6. The incidence of concurrent major arterial occlusion increased as both scores rose. When classified by occluded blood vessel, the incidence of concurrent internal carotid artery occlusion increased as both the CHADS2 and CHA2 DS2 -VASc scores increased. Conclusion: As the CHADS2 and CHA2 DS2 -VASs scores increased, the incidence of concurrent major arterial occlusion, particularly internal carotid artery occlusion, increased in patients with cardioembolic stroke associated with nonvalvular atrial fibrillation.